Karakterizacija s polimeri modificiranih bitumnov z reološkimi preiskavami - Ravnikar Turk, Mojca (Gradbeni vestnik, 2021)
Roads and road asphalt pavements must be resistant to climatic and traffic loads, and maintenance intervals must be as long as possible. Therefore, the oil industry is developing increasingly resistant bitumens for road construction, and at the same time new investigations are being introduced with which we can comprehensively evaluate the behaviour of bitumen. For the characterization of polymer-modified bitumens (PmB), simple investigations, such as softening point and bitumen penetration, which have been used for many years, are not sufficient. For this reason, rheological characteristics should also be determined. A dynamic shear rheometer device is used for bitumen characterization. Viscoelastic and plastic properties of the bitumens are determined on small samples under controlled conditions of stress and deformation. The paper presents the results of traditional as well as rheological tests of polymer-modified bitumens of different strength classes.
Keywords: odprti dostop; open access; polymer-modified bitumen; reologija; rheology; s polimeri modificiran bitumen